Phase 1 and pharmacokinetic study of everolimus in combination with cetuximab and carboplatin for recurrent/metastatic squamous cell carcinoma of the head and neck. Issue 24 (7th August 2014) - Saba, Nabil F.; Hurwitz, Selwyn J.; Magliocca, Kelly; Kim, Sungjin; Owonikoko, Taofeek K.; Harvey, Donald; Ramalingam, Suresh S.; Chen, Zhengjia; Rogerio, Jackie; Mendel, Jennifer; Kono, Scott A.; Lewis, Colleen; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND Platinum‐based therapy combined with cetuximab is standard first‐line therapy for recurrent or metastatic squamous cell carcinoma of the head and neck (RMSCCHN). Preclinical studies have suggested that mammalian target of rapamycin inhibitors may overcome resistance to epidermal growth factor receptor blockers and may augment cetuximab antitumor activity. We conducted a phase 1b trial of carboplatin, cetuximab, and everolimus for untreated RMSCCHN. METHODS Patients received carboplatin (area under the curve = 2 mg/ml/min; 3 weeks on, 1 week off), cetuximab (with a loading dose of 400 mg/m2 and then 250 mg/m2 weekly), and dose‐escalating everolimus (2.5, 5.0, 7.5, and 10 mg/day) with a 3+3 design. After 4 cycles, patients without progression continued cetuximab/everolimus until progression or intolerable toxicity. Patients (age ≥ 18 years) had previously untreated, unresectable RMSCCHN not amenable to radiotherapy and an Eastern Cooperative Oncology Group performance status of 0 to 2. RESULTS The study enrolled 20 patients (male/female = 18/2) with RMSCCHN; the median age was 65 years (44‐75 years). Thirteen patients received everolimus (male/female = 92%). Two of 6 patients receiving 2.5 mg/day experienced dose‐limiting toxicity (DLT) with grade 3 hyponatremia and nausea. In 7 patients receiving de‐escalated everolimus (2.5 mg every other day), grade 3 hyperglycemia produced DLT in 1 of 6 patients. The objective response rate (RR) was 61.5% (all partial responses). Progression‐free survival (PFS) was 8.15 months. The pharmacokinetics of everolimus was described with a 2‐compartment mixed‐effects model. There was a significant correlation between tumor p‐p44/42 staining and response (P = .044) and a marginally significant correlation between phosphorylated mammalian target of rapamycin and overall survival. CONCLUSIONS The maximum tolerated dose of everolimus with cetuximab and carboplatin was 2.5 mg every other day. The regimen was associated with an encouraging RR and PFS, and this suggested possible clinical efficacy in a select group of patients with squamous cell carcinoma of the head and neck. Cancer 2014;120:3940–3951. © 2014 American Cancer Society.